MICROMORPHOLOGICAL CHARACTERISTICS OF VOLCANIC SOILS IN BANTEN AREA - I, FAUZI A.; ZAUYAH, S.; STOOPS, G. (Jurnal Tanah dan Iklim (Indonesian Soil and Climate Journal), 2004)
Four pedons derived from acid and intermediary tuffs in Banten area had been described and sampled for a pedogenesis study. Micromorphological features related to pedogenesis processes were observed through thin sections of some representative horizons using a petrographic microscope. Mineralogical, chemical, and physical data were also used to support interpretation. The results showed that microstructures of soils developed on intermediary tuff had more porous structures and homogenous finemass than those on acid tuff. Groundmass of the soils on intermediary tuff was characterized by dominant fine mass yellowish to reddish brown color, andwith few opaque and weathered minerals. Whereas the soils on the acid tuff had light to strong brown finemass and many coarse quartz particles. Pedofeatures were found as clay coatings on pores especially in the soils with clear dry season climate. Pumice particles and some fresh plagioclase in the surface horizons of the soils was predicted to come from Krakatau ash of the eruption in 1883. Generally, micromorphological, mineralogical,chemical, and physical characteristics of the soils indicated that weathering process and soil genesis more intensive on the intermediary tuff than on the acid tuff. This research is expected to give more knowledge about micromorphological characteristics and pedogenesis processes of the volcanic soils and the influence of Krakatau ash in Banten area.